Ultrasound assisted-phytofabricated Fe3O4 NPs with antioxidant properties and antibacterial effects on growth, biofilm formation, and spreading ability of multidrug resistant bacteria - Mehran Alavi; Naser Karimi (Artificial Cells, Nanomedicine, and Biotechnology, 2019)
Complicated issue in infectious illnesses therapy is increasing of multidrug resistant (MDR) bacteria and biofilms in bacterial infections. In this way, emerging of nanotechnology as a new weapon specifically in the cases of metal nanoparticle (MNPs) synthesis and MNPs surface modification has obtained more attention. In this study, ultrasound-assisted green synthesis method was utilized for the preparation of Fe3O4 NPs with novel shape (dendrimer) through leaf aqueous extract of Artemisia haussknechtii Boiss. Ultraviolet–visible spectroscopy, energy dispersive X-ray spectroscopy (EDX), Fourier transform infrared spectroscopy (FT-IR), scanning electron microscopy (SEM), atomic force microscopic (AFM), X-ray diffraction (XRD) techniques were applied for MNPs physicochemical characterization. Also, disc diffusion assay, minimum inhibitory concentration (MIC), minimum bactericidal concentration (MBC), planktonic and biofilm morphology of three pathogenic bacteria involving Serratia marcescens ATCC 13880, Escherichia coli ATCC 25922, and methicillin-resistant Staphylococcus aureus (MRSA) were evaluated upon treatment of Fe3O4 NPs as antiplanktonic and antibiofilm analysis. Results showed efficient antiplanktonic and antibiofilm activities of biosynthesized Fe3O4 NPs with average diameter size of 83.4 nm. Reduction in biofilm formation of S. aureus ATCC under Fe3O4 NPs stress was significant (66%) in higher MNPs concentration (100 μg/mL). In addition, as first report, spreading ability of S. aureus as important factor in colony expansion on culture medium was reduced by increasing of Fe3O4 NPs. Present study demonstrates striking antiplanktonic, antibiofilm, antispreading mobility and antioxidant aspects of one-pot biosynthesized Fe3O4 NPs with novel shape.